Neuromuscular activity during bench press exercise performed with and without the preexhaustion method - Brennecke, A.; Guimaraes, T. M.; Leone, R.; Cadarci, M.; Mochizuki, L.; Simao, R.; Amadio, A. C.; Serrao, J. (The Journal of Strength and Conditioning Research, 2009)
The purpose of the present study was to investigate the effects of exercise order on the tonic and phasic characteristics of upper-body muscle activity during bench press exercise in trained subjects. The preexhaustion method involves working a muscle or a muscle group combining a single-joint exercise immediately followed by a multi-joint exercise (e.g., flying exercise followed by bench press exercise). Twelve subjects performed 1 set of bench press exercises with and without the preexhaustion method following 2 protocols (P1-flying before bench press; P2-bench press). Both exercises were performed at a load of 10 repetition maximum (10RM). Electromyography (EMG) sampled at 1 kHz was recorded from the pectoralis major (PM), anterior deltoid (DA), and triceps brachii (TB). Kinematic data (60 Hz) were synchronized to define upward and downward phases of exercise. No significant (p > 0.05) changes were seen in tonic control of PM and DA muscles between P1 and P2. However, TB tonic aspect of neurophysiologic behavior of motor units was significantly higher (p < 0.05) during P1. Moreover, phasic control of PM, DA, and TB muscles were not affected (p > 0.05). The kinematic pattern of movement changed as a result of muscular weakness in P1. Angular velocity of the right shoulder performed during the upward phase of the bench press exercise was significantly slower (p < 0.05) during P1. Our results suggest that the strategies set by the central nervous system to provide the performance required by the exercise are held constant throughout the exercise, but the tonic aspects of the central drive are increased so as to adapt to the progressive occurrence of the neuromuscular fatigue. Changes in tonic control as a result of the muscular weakness and fatigue can cause changes in movement techniques. These changes may be related to limited ability to control mechanical loads and mechanical energy transmission to joints and passive structures.